TECHNOLOGY INTEGRATION OF EFFective ENCODING OF THE STREAM OF VIDEO FRAMES TO THE PROCESSING SYSTEM RESOURCES DYNAMIC VIDEO INFORMATION - Баранник, Володимир Вікторович; Шульгін, Сергій Сергійович (Science-based technologies, 2016)
Reasons for need of safety of video information resources for system of objective monitoring and control of strategically significant objects are carried out. An opportunity to increase accessibility and integrity of video information by effective encoding of sequence of frames for a video stream is shown. Importance of a question concerning integration of processes of effective encoding in basic processing systems of dynamic video information flows for reduction of their bit intensity is justified. It is specified that for creation of effective syntax representation it is required to use approach which is based on elimination of interframe redundance taking into account data representation forms at the intraframe level. The main stages of creation of technology of integration of code constructions of effective syntax submission of the normalized of the informative differential described spectrograms of slots of P-frames to structure of a MPEG flow, providing are explained: the given level of integrity of video information; abbreviation of the service data used for flow MPEG; lowering of bit intensity of a video stream. In operation creation of structure of code representation of the closed code video stream including four complex levels of packets of P-frames is carried out: level of the standard unit; level of the integrated macrounit, level of a packet of the P-frame and level of video sequence.